Type and cotype of some Banach spaces - Mieczyslaw Mastylo (International Journal of Mathematics and Mathematical Sciences)
Type and cotype are computed for Banach spaces generated by some positive sublinear operators and Banach function spaces. Applications of the results yield that under certain assumptions Clarkson's inequalities hold in these spaces.